Periodate Oxidation of p-Bromoaniline in Acetone-water medium: A Kinetic Mechanistic Study - Kaushik, R.D.; Dubey, Mukta; P. Singh, Raghvendra; Amrita (Asian Journal of Chemistry, 2016)
Results of kinetic study on the periodate oxidation of p-bromoaniline (PBA) in acetone-water medium have been presented and discussed. Rate law has been derived and mechanism suggested on the basis of various results like first order in each reactant, stoichiometry, thermodynamic parameters, main product identified as 4-bromo-1,2-benzoquinone and various factors influencing the reaction rate such as the effect of pH, dielectric constant, ionic strength and free radical scavengers.